Insect Biodiversity in Corn Plants of Jago 20 Variety in Jombang Regency - Nasirudin, Mohamad; Puspaningrum, Yessita (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
This study aims to determine the biodiversity or diversity of insects in corn plants in the generative phase. This type of research is quantitative descriptive. The study was conducted in systematic and non-systematic land. Sampling of insects in corn plantations in the morning (yellow trap and blue trap), and in the morning, afternoon, and evening (observation). The number of insects obtained was calculated for diversity (H '), dominance (C), and important value index (INP). In systematic land, the H' value of insects was 2.71 while for non-systematic land it was 2.68. The data shows that the insect diversity index is moderate. The dominance index (C) in systematic corn fields in the generative phase of systematic land was 0.074 while in non-systematic land it was 0.072, meaning that both lands showed a low dominance index. In systematic land, the Muscidae family showed an INP of 20.46, for non-systematic land the highest IVI was shown by the Coccinelidae family with a value of 21.42. Generative phase corn fields that use systematic treatment show higher insect diversity compared to generative phase corn fields that use non-systematic treatment. Keywords: Synthetic inorganic, corn, insect diversity.